2015
DOI: 10.1097/mpa.0000000000000251
|View full text |Cite
|
Sign up to set email alerts
|

Population Attributable Risk for Pancreatic Cancer in Northern Italy

Abstract: These results suggest that an appreciable proportion of pancreatic cancers could be avoided in this Italian population by intervention on a few selected modifiable lifestyle factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 41 publications
1
35
0
1
Order By: Relevance
“…By comparison, a population study in Italy estimated that 9•7% of pancreatic cancer occurrence was attributable to diabetes. 33 The US National Cancer Institute estimated that diabetes is associated with a 1•8 times increased risk of pancreatic cancer. 34 From 1980 to 2014, in all countries, diabetes prevalence in adults either increased, especially in low and middle SDI locations, or at best remained unchanged; worldwide, the number of adults with diabetes has quadrupled, 19 so it is expected that diabetes will have a greater contribution to pancreatic cancer occurrence in the future.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, a population study in Italy estimated that 9•7% of pancreatic cancer occurrence was attributable to diabetes. 33 The US National Cancer Institute estimated that diabetes is associated with a 1•8 times increased risk of pancreatic cancer. 34 From 1980 to 2014, in all countries, diabetes prevalence in adults either increased, especially in low and middle SDI locations, or at best remained unchanged; worldwide, the number of adults with diabetes has quadrupled, 19 so it is expected that diabetes will have a greater contribution to pancreatic cancer occurrence in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a summary review of meta-analytical studies showed that the major protective factor is increasing fruit or folate intake, with respective population preventable fractions of 0-12%[70]. In the Italian population, 11.9% of pancreatic cancers were attributable to a low adherence to Mediterranean diet[71]. …”
Section: Etiology and Risk Factorsmentioning
confidence: 99%
“…Both type I and type II diabetes have doubled the risk of pancreatic cancer[72-74]. The pancreatic cancer burden study in the Italian population estimated that 9.7% of pancreatic cancers were attributable to diabetes[71]. The United States National Cancer Institute estimates that diabetes is associated with a 1.8-fold increased risk of pancreatic cancer, particularly in Hispanic men and Asians in comparison with whites and blacks[75].…”
Section: Etiology and Risk Factorsmentioning
confidence: 99%
“…About 95% of pancreatic cancers are ductal adenocarcinomas (PC). Tobacco smoking is the main risk factor for PC and explains about 20% of the risk in a population where prevalence of smoking is 30% 4,5 . ABO non-O blood group, obesity, long-term type 2 diabetes, family history of PC, histories of pancreatitis and possibly heavy alcohol consumption, familial rare inherited mutations in BRCA2 , p16 and other genes, and common variants in at least eight genetic loci are other known PC risk factors 68 .…”
Section: Introductionmentioning
confidence: 99%